MOLECULAR ANALYSIS OF PBMSP-1 GENE IN ERYTHROCYTE OF MICE INFECTED WITH Plasmodium berghei - Rosnizar, Rosnizar; Eriani, Kartini (Universitas Syiah Kuala, 2018)
This study aimed to analyze MSP-1 gene in mice erythrocyte infected with Plasmodium berghei using polymerase chain reaction (PCR). The result showed the existence of 462 bp DNA band which was assumed to encode MSP-1 protein with molecular weight of 19 kDa that can only be found in erythrocyte infected with Plasmodium berghei. BLASTn analysis showed that PbMSP-1 obtained in this study have 100% similar identity with mRNA of PbMSP-1 partial sequence (462 bp), 93% similarity with PbMSP-1 complete sequence (5750 bp and 5376 bp), and 87% similarity with PbMSP-1 incomplete sequence (333 bp).